Co-encapsulation of docetaxel and cyclosporin A into SNEDDS to promote oral cancer chemotherapy. (1st January 2019) - Cui, Weiping; Zhao, Hanqing; Wang, Chen; Chen, Yao; Luo, Cong; Zhang, Shenwu; Sun, Bingjun; He, Zhonggui
Abstract: Self-nanoemulsifying drug delivery system (SNEDDS) have been considered as a promising platform for oral delivery of many BCS (biopharmaceutics classification system) class IV drugs, such as docetaxel (DTX). However, oral chemotherapy with DTX is also restricted by its active P-glycoprotein (P-gp) efflux and hepatic first-pass metabolism. To address these challenges, we developed a novel SNEDDS co-loaded with DTX and cyclosporine A (CsA) to achieve effective inhibition of P-gp efflux and P450 enzyme metabolization, improving oral bioavailability of DTX. The SNEDDS showed uniform droplet size of about 30 nm. Additionally, the prepared SNEDDS exhibited a sequential drug release trend of CsA prior to DTX. The intestinal experiments confirmed that the membrane permeability of DTX was significantly increased in the whole intestinal tract, especially in the jejunum segment. Furthermore, the oral bioavailability of co-loaded SNEDDS was 9.2-fold and 3.4-fold higher than DTX solution and DTX SNEDDS, respectively. More importantly, it exhibited a remarkable antitumor efficacy with a reduced toxicity compared with intravenously administered DTX solution. In summary, DTX-CsA co-loaded SNEDDS is a promising platform to facilitate oral docetaxel-based chemotherapy.